2009
DOI: 10.3357/asem.2444.2009
|View full text |Cite
|
Sign up to set email alerts
|

Crashes of Sightseeing Helicopter Tours in Hawaii

Abstract: Decreases occurred in the overall number and rate of crashes and in ocean crash landings. The increase in VFR-IMC crashes may be related to the requirement that tour helicopters fly at least 1500 ft. above terrain. Attention is still needed to maintenance, pilot training, and restricting flights to operating areas and conditions that enable safe emergency landings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 2 publications
0
17
0
Order By: Relevance
“…A study by Haaland and colleagues cited improper maintenance as the cause of malfunction in 32% of commercial helicopter air tour crashes in Hawaii occurring between 1984 and 2008 (24). Although no studies have reported the combined proportions of helicopter and fixed-wing air tour crashes due to improper maintenance, the NTSB has identified improper maintenance as a precipitating factor in many rotary- and fixed-wing air tour crashes (37).…”
Section: National Transportation Safety Board Recommended Interventionsmentioning
confidence: 99%
See 3 more Smart Citations
“…A study by Haaland and colleagues cited improper maintenance as the cause of malfunction in 32% of commercial helicopter air tour crashes in Hawaii occurring between 1984 and 2008 (24). Although no studies have reported the combined proportions of helicopter and fixed-wing air tour crashes due to improper maintenance, the NTSB has identified improper maintenance as a precipitating factor in many rotary- and fixed-wing air tour crashes (37).…”
Section: National Transportation Safety Board Recommended Interventionsmentioning
confidence: 99%
“…The Part 91 air tour crash rate of 3.5 per 100,000 h flown is similar to the reported crash rates in categories considered to be “high hazard” commercial aviation. Prior to 1994, the Hawaiian helicopter air tour crash rate of 3.4 per 100,000 flight hours was so alarming that it prompted the emergency implementation of Special Federal Avia tion Regulation 71 by the FAA (24). Similarly, the Helicopter Emergency Medical Services crash rate of 3.5 per 100,000 h flown between the years 1992 and 2001 prompted a special investigation by the NTSB in 2009 (2, 42).…”
Section: Summary Of Adequacy Of Responses and Recommendationsmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3][4][5][6][7] However, the helicopter's flying behavior may be affected by many potential obstacles in the low airspace (e.g. telephone pole, electric wire, etc.)…”
Section: Introductionmentioning
confidence: 99%